Climate change adaptation exertions on the use of alternative water resources in Antalya, Türkiye - Kilinc, Elif Ayyuce; Tanik, Aysegul; Hanedar, Asude; Gorgun, Erdem (Frontiers in Environmental Science, 2023)
The intention of this study is to present the payback periods of applying rainwater harvesting and/or grey water reuse systems as alternative water resources in different building typologies; hospital, a shopping mall and a hotel under operation in Antalya Province of Türkiye. Significance of the work done through the cost-benefit analyses for the selected case studies lays on the water savings while serving to four of the sustainable development goals, namely clean water and sanitation, sustainable cities and communities, responsible consumption and production, and climate action. These efforts may be considered as valuable urban-based solutions towards the climate change effects that have already taken its place among the main environmental problems all around the world. Thorough surveys on the existing selected typologies are conducted regarding their water consumption and probable water savings via reuse activities. As-built plumbing projects and plans are also investigated during the accomplishment of the comprehensive design work leading to calculation of the total investment and operation costs of the rainwater harvesting and grey water reuse practices. The real up-to-date prices in euro currency are used to make the results more meaningful by the interested parties. Selected typologies are undergone to cost-benefit analysis for both of the alternative water reuse systems. The payback periods are calculated as 6, 2, and 9 years for rainwater harvesting, and as 5, 6 and 9 years for grey water reuse for the hospital, shopping mall and the hotel, respectively. Both of the systems are performed for the shopping mall simultaneously and the resulting payback period is found as 5 years. Information on the amortization periods in literature states that less than a decade demonstrates achievable and acceptable applications. As such, the design attempts also correlated these findings. However, feasibility of these practices may be increased by encouraging public on their utility and benefit on water savings. As is the case in developed countries, incentives like tax reductions and exemptions may be realized to achieve applicability of these alternative technologies. The topic of concern is among the leading environmental problems of the world due to climate change effects on especially water resources.